A meta-analysis of weight gain in first year university students: is freshman 15 a myth? - Vadeboncoeur, Claudia (BMC Obes, 2015)
BACKGROUND: Observational studies report that as students transfer from secondary school to university, there is a tendency to gain weight. This phenomenon is known as the “Freshman 15” in North America, referring to the claim that on average weight gain is 15 lb (6.8 kg) in the first year of university. Studies since 1985 have mostly found weight gains ranging from 1 kg to 6 kg. Our meta-analysis aimed to update the literature on the “Freshman 15” in the first year of university. We also aimed to explore weight gain in only those who gained weight and perform several subgroup analyses. Given adolescent weight gain is highly linked to overweight and obesity in adults, a better understanding of university student weight gain is crucial if we are to combat the rising adult obesity prevalence. METHODS: We conducted a search on six standard electronic databases (including PubMed, Embase, PsycInfo) from 1980 to 2014. Only peer reviewed articles with data from longitudinal studies were included. Screening was performed by two reviewers. The quality of papers was assessed and data extraction was done with a systematic approach. RESULTS: Thirty two studies were included and 22 studies (5549 students) were included in a pooled mean meta-analysis as they reported standard errors. The overall pooled mean weight gain was 1.36 kg (3lbs) (95 % CI: 1.15 – 1.57) over an average of 5 months. A majority of students, 60.9 %, gained weight during freshman year and these on average gained 3.38 kg (7.5lbs) (95 % CI: 2.85 – 3.92). CONCLUSION: Freshman weight gain is an issue with almost two thirds of students gaining weight. Students who gained weight, gained it at rates much faster than in the general population. Despite most universities having some health promotion policies, we denote a consistent weight gain in university students across several countries.